Pengaruh Persepsi Harga, Word of Mouth, Servicescape dan Kepercayaan Konsumen terhadap Kepuasan Konsumen pada Suzuya Hotel Rantauprapat - Putri Medina Ginting; Marlina Siregar; Raja Saul Marto Hendry (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This study aims to determine and analyze the influence of price perception, word of mouth, servicescape, and consumer trust on customer satisfaction at Suzuya Hotel Rantauprapat. This research employs a quantitative approach to systematically investigate the relationships among the selected variables. The participants of the study were customers of Suzuya Hotel Rantauprapat, and the Lemeshow formula was applied to determine the sample size due to an unknown total population. A total of 96 respondents participated in this study. Data collection methods included observation, documentation, and the administration of a structured Likert-scale questionnaire. Prior to hypothesis testing, traditional assumption tests such as data normality, heteroscedasticity, and multicollinearity were performed to ensure the validity of the regression analysis. Multiple linear regression analysis was conducted using the coefficient of determination (R²), partial (t) tests, and simultaneous (F) tests. The findings demonstrate that price perception, word of mouth, servicescape, and consumer trust each have significant partial effects on customer satisfaction, while collectively they exert a substantial simultaneous influence. These results highlight the importance of strategic pricing, positive customer communication, quality service environments, and trust-building efforts in enhancing overall customer satisfaction at Suzuya Hotel Rantauprapat.